Debt Relief and Good Governance: New Evidence - Andreas Freytag; Jonatan Pettersson; Julian Schmied (Center for Economic Studies and ifo Institute (CESifo), 2017)
Since the introduction of the HIPC Initiative in the early 2000s, indebted LICs had to show a decent governance performance before their debts were forgiven. We discuss the hypothesis that during the follow-up, Multilateral Debt Relief Initiative (MDRI), the World Bank has refrained from this policy, and that debt relief decisions are rather politically driven. We test different political economy theories by applying panel models to a set of debtor and creditor countries, respectively. Our main finding shows, that improvements in governance quality led to higher levels of debt forgiveness in 2000-2004, but not in the subsequent periods.
Keywords: O20; 330; debt relief; World Bank; MDRI; HIPC; political economy; development aid